2009
DOI: 10.1126/science.1171242
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Gene Therapy with a Lentiviral Vector in X-Linked Adrenoleukodystrophy

Abstract: X-linked adrenoleukodystrophy (ALD) is a severe brain demyelinating disease in boys that is caused by a deficiency in ALD protein, an adenosine triphosphate-binding cassette transporter encoded by the ABCD1 gene. ALD progression can be halted by allogeneic hematopoietic cell transplantation (HCT). We initiated a gene therapy trial in two ALD patients for whom there were no matched donors. Autologous CD34+ cells were removed from the patients, genetically corrected ex vivo with a lentiviral vector encoding wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
981
0
30

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,369 publications
(1,049 citation statements)
references
References 25 publications
19
981
0
30
Order By: Relevance
“…Encouraging results were obtained in a clinical trial using lentiviral vectors, with integration in specific genomic regions not associated with oncogenic selection. 44,45 The availability of Brtl mice will allow us to test such an approach for siRNA delivery by transducing Brtl mesenchymal stem cells with the lentiviral vector expressing the effective F-shRNA and transplanting them back to Brtl, as previously described. 20 Other novel tools may allow us to more safely manipulate mammalian cells than the use of lentivirus vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results were obtained in a clinical trial using lentiviral vectors, with integration in specific genomic regions not associated with oncogenic selection. 44,45 The availability of Brtl mice will allow us to test such an approach for siRNA delivery by transducing Brtl mesenchymal stem cells with the lentiviral vector expressing the effective F-shRNA and transplanting them back to Brtl, as previously described. 20 Other novel tools may allow us to more safely manipulate mammalian cells than the use of lentivirus vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, HSC gene therapy using a lentiviral vector has been reported to be successful in arresting the progression of CCALD in two patients at an early stage, 11 however, the mechanisms of the therapeutic effect in this therapy still remain obscure, which may be because of replacement of the ABCD1 gene, that of normal stem cells or other factors. Further studies concerning the modulation of VLCFA or the prevention of cerebral involvement should be accelerated for suffering patients and their families, as well as the identification of predictive factors for the onset of brain involvement as the keys to solving the problems.…”
Section: Early Intervention and Long-term Follow-up System For Presymmentioning
confidence: 99%
“…[28] Another successful use of lentiviral vector in a clinical trial was reported for the treatment of X-linked adrenoleukodystrophy due to a deficiency of the ABCD1 gene. [29] In this trial, progressive cerebral demyelination in two patients was successfully blocked for 14-16 months after lentiviral delivery of wild-type ABCD1 to CD34+ cells ex vivo. [29] These results encourage more clinical investigation into the use of lentiviral vectors for human gene therapy.…”
Section: Lentiviralmentioning
confidence: 95%
“…[29] In this trial, progressive cerebral demyelination in two patients was successfully blocked for 14-16 months after lentiviral delivery of wild-type ABCD1 to CD34+ cells ex vivo. [29] These results encourage more clinical investigation into the use of lentiviral vectors for human gene therapy.…”
Section: Lentiviralmentioning
confidence: 95%